ANALISA PENGARUH VEGETASI TERHADAP TINGKAT KEBISINGAN DI SEPANJANG JALAN RAYA PEKANBARU-BANGKINANG - Azura '; Erwin '; Defrianto ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
The influence of vegetation such as ketapang, sengon, mango, of acacia, durian andpalm along Pekanbaru-Bangkinang highway against noise level has been studied. Noisesource was originated from sound of vehicles passing through the highway. An instrument used to record the noise level in the study is Sound Level Meter (SLM). In order to obtain the absoption of noise level, then it was used 2 SLMs. The first SLMwas utilized to record the noise directly generated by vehicles without any obstaclesand the second SLM was located behind the trees as sound obstacles. The position ofthose two SLMs was arranged along the road with the distance of about 15 m from thehighway. The next measurement was to record the noise level for one day started from7: 00 a.m until 6: 00 p.m along the highway. The influence of the distance against thenoise level was also studied. The result of this research showed that palm trees has thehighest effect on noise reduction and followed by acacia, mango, durian, sengon andketapang trees. The high absorption of sound by palm tree of about 6.092% because the volume of the palm leaves per percentage of the absorption is smaller compared tothose for other vegetations. These results were compared to those of Maekawa andISO9613 calculation. From the comparison, it was obtained that Maekawa calculation ishigher compared to those of this research, while the ISO9613 calculation was lower.The error percentage of the calculation for Maekawa and ISO9613 was 6.82% and8.76% respectively. The profile of one day noise along the highway as a function of time showed that there were two peaks of noise that were occurred at 09.00-10.00 and17.00-18.00. Moreover, the noise level was reduced very significantly from 71.90dB(A) to 63.58 dB(A) as the measurement away from the noise source.